Mengukur Kinerja Keuangan Perusahaan Rokok dengan MVA dan CVA - Umi Achyatun, Rismawati; Wijayanto, Edi; Widiyati, Sri (Sekolah Tinggi Ilmu Ekonomi Mahaputra Riau, 2025)
This research aims to determine financial performance using the Market Value Added (MVA) and Cash Value Added (CVA) in cigarette companies listed on the Indonesian Stock Exchange in 2019-2023. This research was conducted to determine the magnitude of creation the added value of wealth and the added value of cash that the company has generated for its holders share. This type of research is descriptive applied quantitative research. The data collection method used is the documentation method using cigarette company financial report data. The research sample was selected using a purposive sampling method with a total sample of 3 companies Tobacco subsector listed on the IDX for the 2019-2023 period 5 years time. The analytical tool used in this research uses the Market Value Added (MVA) and Cash Value Added (CVA). The results of the research can be seen that The MVA and CVA values ​​for each company fluctuate and vary, where the average value is MVA has a positive value, which means the company has been able to increase the value of its capital entered. Based on the average CVA value, it is positive, which means the company is capable generate cash from one period to the next. Overall company performance The tobacco subsector is in good condition because the industry's average MVA and CVA values ​​are valuable positive.